Bilingualism as a risk factor for false reports of stuttering in the Early Childhood Longitudinal Study (ECLS-K:2011) - Gahl, Susanne (Frontiers in Psychology, 2023)
Bilingualism has historically been claimed to be a risk factor for developmental stuttering. Here, we analyze data from monolingual and bilingual children in grades Kindergarten-5, using the Early Childhood Longitudinal Study, Kindergarten Class of 2010-11 (ECLS-K:2011). We find that the prevalence, as well as the male/female ratio of reported stuttering in the ECLS are inconsistent with clinical reports of stuttering. We argue that the reported figures are unlikely to actually reflect stuttering. We discuss some possible factors that may inflate the reported prevalence, including a persistent belief that bilingualism might be a risk factor, a lack of awareness of the difference between stuttering vs. normal disfluencies, and the informal usage of the word "stuttering" on the part of teachers and parents to describe typical disfluencies.